2012
DOI: 10.3182/20120328-3-it-3014.00021
|View full text |Cite
|
Sign up to set email alerts
|

The Next Generation of Relay-Based PID Autotuners (PART 1): Some Insights on the Performance of Simple Relay-Based PID Autotuners

Abstract: The paper presents theoretical insights which might lead to further development of improved relay-based PID autotuners. The analysis is based on the first generation of autotuners, namely the widely used Åström-Hägglund relay-feedback tuner. The analysis is accompanied by illustrative examples. The performance of the autotuners is evaluated against a reference PID controller which is designed using computer aided design tools and assuming full knowledge of the system's transfer function. The paper is concluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…It can be observed that in this case the autotuner fails to give a satisfactory performance. This behaviour is not specific for the example from (2); it is generally valid for integrating processes; it can also be explained via theoretical insight (Ionescu and De Keyser, 2012 First the PM autotuner is tested on the example (2), for which the AH tuner did not give satisfactory responses. Fig.…”
Section: Limitations Of Simple Autotunersmentioning
confidence: 98%
See 1 more Smart Citation
“…It can be observed that in this case the autotuner fails to give a satisfactory performance. This behaviour is not specific for the example from (2); it is generally valid for integrating processes; it can also be explained via theoretical insight (Ionescu and De Keyser, 2012 First the PM autotuner is tested on the example (2), for which the AH tuner did not give satisfactory responses. Fig.…”
Section: Limitations Of Simple Autotunersmentioning
confidence: 98%
“…IFAC Conference on Advances in PID Control PID'12 Brescia (Italy), March 28-30, 2012 WeB1.6 Again, this behaviour is not specific for the example (3); it is a generally valid observation that the PM autotuner gives poor results for processes with significant time delay; it can be explained via theoretical insight why this is the case (Ionescu and De Keyser, 2012). An interesting fact to notice is that the AH autotuner will give excellent results for the system (3).…”
Section: Limitations Of Simple Autotunersmentioning
confidence: 98%
“…for the original AH-tuner, the beeline of C * P goes through the specific point −0.6−0.28j (distance to the point -1 is then 0.5). The insights from [10] show that specification of only 1 point in the Nyquist plane might be sufficient for some type of processes, but might as well result in poor (low) modulus margin for other types of processes.…”
Section: Proposed Autotuning Algorithmmentioning
confidence: 99%
“…Classical PID autotuning approaches such as the Astrom-Hagglund (AH) autotuner and Phase Margin (PM) autotuner [7,8,9,10], identify the critical point on the process frequency response using such relay feedback. Their advantage is that they are very simple to apply, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Classical PID autotuning approaches such as theÅström-Hägglund (AH), Ziegler-Nichols and recent revisited algorithms based on phase margin specifications (Åström and Hägglund (2006); Hang et al (1991); Ionescu and De Keyser (2012)), identify the critical point on the process CM Ionescu is a post-doctoral fellow of Flanders Research Foundation, grant nr 12B3415N. All authors are members in the EEDT group, partner of Flanders Make consortium: www.eedt.ugent.be.…”
Section: Introductionmentioning
confidence: 99%